Rootstock–Scion Interaction Affects Cadmium Accumulation and Tolerance of Malus - He, Jiali; Zhou, Jiangtao; Wan, Huixue; Zhuang, Xiaolei; Li, Huifeng; Qin, Sijun; Lyu, Deguo (Frontiers in Plant Science, 2020)
To understand the roles of Malus rootstock, scion, and their interaction in Cd accumulation and tolerance, four rootstock-scion combinations consisting of the apple cultivars ‘Hanfu’ (HF) and ‘Fuji’ (FJ) grafted onto M. baccata (Mb) or M. micromalus ‘qingzhoulinqin’ (Mm) rootstocks differing in relative Cd tolerance were exposed either to 0 µM or 50 µM CdCl2 for 18 d. Cd accumulation and tolerance in grafted Malus plants varied within rootstock, scion, and rootstock-scion interaction. Cd-induced decreases in photosynthesis, photosynthetic pigment level, and biomass were lower for HF grafted onto Mb than those for HF grafted onto Mm. Reductions in growth and photosynthetic rate were always the lowest for HF/Mb. Cd concentration, bioconcentration factor (BCF), and translocation factor (Tf) were always comparatively higher in HF and FJ grafted onto rootstock Mm than in HF and FJ grafted on Mb, respectively. When HF and FJ were grafted onto the same rootstock, the root Cd concentrations were always higher in HF than FJ, whereas the shoot Cd concentrations displayed the opposite trend. The shoot Cd concentrations and Tf were lower for HF/Mb than the other rootstock-scion combinations. Rootstock, scion, and rootstock-scion interaction also affected subcellular Cd distribution. Immobilization of Cd in the root cell walls may be a primary Cd mobility and toxicity reduction strategy in Malus. The rootstock and scion also had statistically significant influences on ROS level and antioxidant activity. Cd induced more severe oxidative stress in HF and FJ grafted onto Mm than it did in HF and FJ grafted onto Mb. Compared with FJ, HF had lower foliar O2-, root H2O2, and root and leaf MDA levels, but higher ROS-scavenging capacity. The rootstock, scion, and rootstock-scion interaction affected the mRNA transcript levels of several genes involved in Cd uptake, transport, and detoxification including HA7, FRO2-like, NRAMP1, NRAMP3, HMA4, MT2, NAS1, and ABCC1. Hence, the responses of grafted Malus plants to Cd toxicity vary with rootstock, scion, and rootstock-scion interaction.